Disentangling the relationship between tumor genetic programs and immune responsiveness. (April 2016) - Bedognetti, Davide; Hendrickx, Wouter; Ceccarelli, Michele; Miller, Lance D; Seliger, Barbara
Highlights: The Th-1 cancer phenotype is characterized by responsiveness to immunotherapy. This phenotype is accompanied by activation of counter-regulatory mechanisms. Tumor genetic program modulates the development of the Th-1 cancer phenotype. Oncogenic pathways can be targeted to enhance the efficacy of cancer immunotherapy. Abstract : Correlative studies in humans have demonstrated that an active immune microenvironment characterized by the presence of a T-helper 1 immune response typifies a tumor phenotype associated with better outcome and increased responsiveness to immune manipulation. This phenotype also signifies the counter activation of immune-regulatory mechanisms. Variables modulating the development of an effective anti-tumor immune response are increasingly scrutinized as potential therapeutic targets. Genetic alterations of cancer cells that functionally influence intratumoral immune response include mutational load, specific mutations of genes involved in oncogenic pathways and copy number aberrations involving chemokine and cytokine genes. Inhibiting oncogenic pathways that prevent the development of the immune-favorable cancer phenotype may complement modern immunotherapeutic approaches.